Advancements in Buccal Drug Delivery: Polymers and Their Applications - Shardor Ambarish G; Siddramappa B Shirsand; Anand Kumar Yegnoor (RGUHS Journal of Pharmaceutical Sciences)
Buccal drug delivery offers a promising alternative to conventional oral routes by facilitating the rapid and efficient absorption of therapeutics directly through the mucosal tissues lining the oral cavity. This review explores the significant advancements in buccal drug delivery systems emphasizing the polymers used for enhancing drug efficacy and patient compliance. We examine the characteristics of various polymers that make them suitable for buccal applications such as mucoadhesion biocompatibility and controlled release capabilities. Recent innovations in polymer technology have led to the development of more sophisticated buccal delivery systems capable of overcoming the challenges of enzymatic degradation and permeability barriers. The review also discusses the future directions of buccal drug delivery systems BDDS highlighting the potential for integrating novel polymers and technology to improve therapeutic outcomes. Through a detailed evaluation of current literature and emerging trends this paper aims to provide insight into the evolving landscape of buccal drug delivery BDD and its implications for the pharmaceutical industry.